Mitral annulus disjunction with cardiac arrythmia: Case report (Research, Society and Development, 2024)
Mitral annular disjunction is a structural change resulting from the abnormal insertion of the mitral annular flexion line into the mitral wall. Patients with this alteration are more likely to develop arrhythmogenic syndromes, syncope, and even sudden death. This condition is still little known, but it has gained prominence as diagnostic imaging methods become more accessible. The present study, conducted through a review of medical records at the Maria Pedrossian University Hospital, aims to describe and discuss the case of a young, previously healthy patient who presented sporadic palpitations during an outpatient consultation. The electrocardiogram showed isolated ventricular extrasystole, the echocardiogram did not meet the criteria for mitral valve prolapse, and after the investigation progressed, with the aid of cardiac resonance, a diagnosis of mitral annular disjunction was made. After diagnosis, although the therapeutic approach is still uncertain in the medical literature, symptomatic treatment with beta-blockers was initiated, with improvement of symptoms. Thus, it is concluded that it is important to disclose mitral annular disjunction as a differential diagnosis among patients with ventricular arrhythmias so that the investigation can continue, as this condition is potentially fatal and requires regular medical follow-up as a way of preventing sudden death in patients.